POLA PENGGUNAAN ANTIBIOTIK PADA PASIEN TUBERKULOSIS DI PUSKESMAS PEKKAE KABUPATEN BARRU SULAWESI SELATAN PERIODE JANUARI – DESEMBER 2022 - Yuliana, Dewi; Putra, Bayu; Syahrul, Andi Ahmad (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
ANDI AHMAD SYAHRUL, This study aims to determine the pattern of antibiotic use in tuberculosis patients at the Pekkae Health Center, Barru in 2022. The method used is an observation method using a sampling technique, namely total sampling. The results showed that the dominant male patients were 59.1%; aged 45-54 and 55-64 as much as 22.72%. The use of drugs was adjusted to the patient's weight with intensive phase treatment of 3 2KDT tablets which was 50% then 4 4KDT tablets and 4 2KDT tables which were 27.27% then 3 4KDT tablets and 4 2KDT tablets which were 13.63% and 2 4KDT tablets and 2 2KDT tablets as much as 9.1%. The conclusion in this study is that the use and suitability of OAT is based on the TB control guidelines of the Indonesian Ministry of Health in 2016, which was used in 3 patients who had an increase in the number of tablets taken in combination doses and 1 patient there was a decrease in the number of tablets taken in combination doses and the pattern of using drugs with a fixed dose combination containing rifampicin 150 mg, isoniazid 75 mg, pyrazinamide 400mg, ethambutol 275 mg